Histological and biofilm change at the infected wound bed after treatment with Polyhexamethylene biguanide (latex HB®) - Nguyen, Tien Dung; Tuong, Phi Vuong; Chu, Anh Tuan (Tạp chí Y học Thảm hoạ và Bỏng, 2024)
Objective: Evaluation of the effect of PBH (PBH) on histopathological and biofilm change at the infected wound bed.Subjects and methods: Fifteen infected wounds of 15 inpatients at the Wound Healing Center - National Burn Hospital, from July to August 2024. The wounds were washed by PBH. Evaluation of histological progression on H&E-stained slides and Biofilm on the wound bed using scanning electron microscopy (SEM), at the time before (T0), after 7 days (T1) and after 14 days (T2) using PBH.Results: The extracellular matrix structure at the wound site showed reduced inflammation, with a statistically significant decrease in the number of inflammatory cells at times T1 and T2. The proportion of wounds with biofilm decreased from 50% at T0 to 20.8% at time T1 and 8.3% at time T2. The biofilm structure was disrupted and eliminated at times T1 and T2 when observed under SEM.Conclusion: PBH effectively eliminates bacteria, disrupts biofilm, and promotes wound healing.